Design of capacitive micromachined ultrasonic transducer (CMUT) linear array for underwater imaging. Issue 1 (18th January 2016) - Zhang, Rui; Zhang, Wendong; He, Changde; Song, Jinlong; Mu, Linfeng; Cui, Juan; Zhang, Yongmei; Xue, Chenyang
Abstract : Purpose: – The purpose of this paper was to develop a novel capacitive micromachined ultrasonic transducer (CMUT) reception and transmission linear array for underwater imaging at 400 kHz. Compared with traditional CMUTs, the developed transducer array offers higher electromechanical coupling coefficient and higher directivity performance. Design/methodology/approach: – The configuration of the newly developed CMUT reception and transmission array was determined by the authors' previous research into new element structures with patterned top electrodes and into directivity simulation analysis. Using the Si-Silicon on insulator (Si-SOI) bonding technique and the principle of acoustic impedance matching, the CMUT array was fabricated and packaged. In addition, underwater imaging system design and testing based on the packaged CMUT 1 × 16 array were completed. Findings: – The simulation results showed that the optimized CMUT array configuration was selected. Furthermore, the designed configuration of the CMUT 1 × 16 linear array was good enough to guarantee high angular resolution. The underwater experiments were conducted to demonstrate that this CMUT array can be of great benefit in imaging applications. Practical implications: – Based on our research, the CMUT linear array has good directivity and good impedance matching with water and can be used for obstacle avoidance, distance measurement and imaging underwater. Originality/value: – This research provides a basis for CMUT directivity theory and array design. CMUT array presented in this paper has good directivity and has been applied in the underwater imaging, resulting in a huge market potential in underwater detection systems.